2020
DOI: 10.1037/xan0000246
|View full text |Cite
|
Sign up to set email alerts
|

Geometry learning while navigating: The importance of task difficulty and sex differences.

Abstract: Cheng (1986) trained male rats to search for food in a rectangular arena that also contained distinctive visual patterns. He found that the rats used mainly the geometric framework of the box itself to find the food and claimed that geometrical information is processed in a specialized module, which is independent of feature information. The aim of the present set of experiments was to check if the previous results with male rats and an appetitive task could be extended to an aversive task while using both mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…The results of Experiment 2A revealed that males and females did not differ in the initial learning speed to find the hidden platform in the Morris pool, neither during the pre-training escape trials, in the circular pool in the absence of the landmark, nor in the subsequent training phases with the hidden platform located in a certain corner of the kite-shaped pool (Training 1), of the rectangular-shaped pool (Training 2), and of the triangular-shaped pool–in the last case close to the landmark (Training 3). This suggests that females do not spend more time exploring the pool than males, but that both males and females seem to swim directly to the platform (see Forcano et al, 2009 and Chamizo et al, 2020 for similar results). The most relevant result of Experiment 2A is the shape test trial, without the platform (i.e., in the triangular pool and no landmark).…”
Section: Discussionmentioning
confidence: 81%
See 4 more Smart Citations
“…The results of Experiment 2A revealed that males and females did not differ in the initial learning speed to find the hidden platform in the Morris pool, neither during the pre-training escape trials, in the circular pool in the absence of the landmark, nor in the subsequent training phases with the hidden platform located in a certain corner of the kite-shaped pool (Training 1), of the rectangular-shaped pool (Training 2), and of the triangular-shaped pool–in the last case close to the landmark (Training 3). This suggests that females do not spend more time exploring the pool than males, but that both males and females seem to swim directly to the platform (see Forcano et al, 2009 and Chamizo et al, 2020 for similar results). The most relevant result of Experiment 2A is the shape test trial, without the platform (i.e., in the triangular pool and no landmark).…”
Section: Discussionmentioning
confidence: 81%
“…However, a recent set of experiments by Chamizo et al (2020) , using male and female rats and several modified Morris pools (as in the wet condition of Golob and Taube’s, 2002 ), has shown that both male and female rats primarily encode geometric information even when trained in the presence of salient visual cues, thus supporting Cheng’s initial results ( Cheng, 1986 ; see also Gallistel, 1990 ). In Experiments 1 and 2 of the study by Chamizo et al (2020) , male and female rats were trained in a modified pool (i.e., with a rectangular shape) to find a hidden platform, which was located based on two cues or sources of information, both next to the platform: one specific landmark (a target landmark), outside the pool, and one particular corner of the pool (a target corner). In both experiments the results revealed that geometry learning had clearly interfered with learning about the target landmark.…”
Section: Introductionmentioning
confidence: 72%
See 3 more Smart Citations